THE GOVERNMENT ABILITY OF KIM JONG IL FOR NUCLEAR DEVELOPMENT IN KOREA UTARA AT 1998-2008 - Ferawati, Anita nita (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret)
North Korea is a country located in the northern part of the Korean peninsula at latitude 37° 43° N and longitude 124° 131° E. In North Korea, all residents must follow the draft. Military force was formed to protect North Korea from attacks another country, and as one of the policy to cover the hunger problem in the country due to the bad economy. The head of government is the first North Korea Kim Il Sung, who was a freedom fighter. Around 1990, Kim Il Sung died of the World. Before his death, the government has handed over to Kim Jong Il. Kim Jong Il was born in the Soviet time parents fought Japanese troops in North Korea. After four years, Kim Jong Il returned to Pyongyang. In 1998, Kim was inaugurated as the position of the highest positions in the State of North Korea (Selig. S. Harrison. 2002). North Korea to modernize the country by focusing the power of the state in economic planning, heavy industry and military development. North Korea improve the economy by developing nuclear energy instead of electric energy. In addition, the development of nuclear energy has the objective for national defense and security (Kompas, May 12, 2003). However, the United States was worried about North Korea's nuclear development program because it can threaten the stability of the Korean Peninsula. For the United States the North Korean nuclear issue to be taken seriously, so that the United States tried to pressure North Korea to halt its nuclear development program (Tempo, February 12, 1994). Through economic ties and integration with the international North Korea Pyongyang aims to have awareness of the importance of maintaining regional and international peace, including with South Korea. Key words: North Korea's nuclear development program, international relations.